1989
DOI: 10.1161/01.res.65.5.1263
|View full text |Cite
|
Sign up to set email alerts
|

Degree and time sequence of hypothermic protection against experimental ischemic acute renal failure.

Abstract: The purpose of this study was to assess the degree, time sequence, and biochemical correlates of hypothermic protection against ischemic acute renal failure. Rats subjected to 40 minutes of bilateral renal artery occlusion (RAO) were made mildly hypothermic (32 degrees-33 degrees C, by cold saline peritoneal lavage) during the following time periods: 1) RAO only, 2) reperfusion only (beginning at 0, 15, 30, or 60 minutes after RAO and maintained for 45 minutes), or 3) during and after (0-45 minutes) RAO. Conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 15 publications
0
29
0
2
Order By: Relevance
“…Recent studies have shown the critical eÂect that not significantly diÂerent (P=0.20) from that observed in the IP-only animals (group B). There was no significhanges in core temperature can have on renal preservation [19]. Thus, a decrease of just 2°C can result cant diÂerence between grades of ischaemic damage in group C (RI only) compared with group D (IP+RI) for in significant reductions in ischaemic damage [20].…”
Section: Dmsa Imagingmentioning
confidence: 99%
“…Recent studies have shown the critical eÂect that not significantly diÂerent (P=0.20) from that observed in the IP-only animals (group B). There was no significhanges in core temperature can have on renal preservation [19]. Thus, a decrease of just 2°C can result cant diÂerence between grades of ischaemic damage in group C (RI only) compared with group D (IP+RI) for in significant reductions in ischaemic damage [20].…”
Section: Dmsa Imagingmentioning
confidence: 99%
“…There further have been historical reports of hypothermia conditioning against ischemia, and to a lesser extent reperfusion, in a murine model. 5 …”
mentioning
confidence: 99%
“…Renal oxygen consumption is reduced to 40% when the renal parenchyma is cooled to 30°C, to 15% at 20°C, and to Ͻ5% at 10°C (6,11,20,39,49). Also, milder disruption in proximal tubules has been seen after 48 h of cold ischemia compared with warm ischemia (48), but glomerular podocytes and peritubular endothelial cells were damaged after cold ischemia.…”
Section: Discussionmentioning
confidence: 99%